Egg Chip Quality with Different Types and Levels of Fillers - Kartina Kartina; Nahariah Nahariah; Fatma Maruddin; Hikmah M Ali (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2020)
Infertile egg generally only be industrial waste hatching so that the necessary efforts to improve its quality. This can be done by processing. One of them is a chips product, the product resembles a thin plat, small and solid. This studies aim to determine the physicochemical quality of egg chips. The study used a completely randomized design factorial pattern 3x3. Factor A was the type of filler including soy powder, tapioca powder, and a combination of both. Factor B is filler level (%) 0, 3 and 6. The parameters are testing of hardness, friability, solubility and moisture content. The results showed that the types of filler had a very significant effect (P <0.01) on dissolution time. Addition of filler level significantly affected (P <0.05) on hardness, friability and solubility. There is an interaction between types and levels of filler material against hardness and solubility. The addition of tapioca powder at the level of 3% in making egg chips can be increasing hardness, not fragile, solubility time of fast. But the egg chip does not experience changes in water content.